Effects of early maternal care on anxiety and threat learning in adolescent nonhuman primates - Elyse L. Morin; Erin R. Siebert; Brittany R. Howell; Melinda Higgins; Tanja Jovanovic; Andrew M. Kazama; Mar M. Sanchez (Developmental Cognitive Neuroscience)
Early life adverse experiences, including childhood maltreatment, are major risk factors for psychopathology, including anxiety disorders with dysregulated fear responses. Consistent with human studies, maltreatment by the mother (MALT) leads to increased emotional reactivity in rhesus monkey infants. Whether this persists and results in altered emotion regulation, due to enhanced fear learning or impaired utilization of safety signals as shown in human stress-related disorders, is unclear. Here we used a rhesus model of MALT to examine long-term effects on state anxiety and threat/safety learning in 25 adolescents, using a fear conditioning paradigm (AX+/BX-) with acoustic startle amplitude as the peripheral measure. The AX+/BX- paradigm measures baseline startle, fear-potentiated startle, threat/safety cue discrimination, startle attenuation by safety signals, and extinction. Baseline startle was higher in MALT animals, suggesting elevated state anxiety. No differences in threat learning, or threat/safety discrimination were detected. However, MALT animals showed generalized blunted responses to the conditioned threat cue, regardless of the safety cue presence in the transfer test, and took longer to extinguish spontaneously recovered threat. These findings suggest adverse caregiving experiences have long-term impacts on adolescent emotion regulation, including elevated state anxiety and blunted fear conditioning responses, consistent with reports in children with maltreatment exposure.